(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
To this day, the experience of nations that have achieved and maintained economic stability demonstrates that an improved level of knowledge among the populace is one of the primary pillars around which economic stability is built. In light of this, it is abundantly evident that the primary strategic priority of any state ought to be in the area of improving people’s access to educational systems and technology, and this should be the case regardless of the people’s age as well as their social and economic standing. It is required to establish a distant education infrastructure that is of a high quality in order to find a solution to this problem.